Burden of sickle cell anemia in Africa: A systematic review and meta-analysis - Bwambale Jonani; Emmanuel Charles Kasule; Bwire Roman Herman; Joel Fredrick Arturo; Mwesigwa Calvin Mugambwa; Ssebulime Stephen; John Bosco Mundaka; Richard Kwizera; Gerald Mboowa; Felix Bongomin (PLoS ONE, 2025)
Introduction Sickle Cell Anemia (SCA) is a significant genetic disorder in Africa; however, comprehensive data on its prevalence and geographic distribution remain limited. We aimed to estimate the pooled prevalence of SCA (HbSS) in African populations and examine regional, demographic, and temporal variations from 1994–2024. Methods We systematically searched PubMed, Scopus, Google Scholar, and BASE databases for studies reporting SCA prevalence in African populations. Screening and quality assessments were performed using JBI tools. A random-effects meta-analysis with logit transformation was performed, with subgroup analyses by region, age, sex, and study design. Meta-regression explored heterogeneity sources, including geographic region, age category, diagnostic method, study design, and publication year. Results From 115 studies with 1,203,839 participants and 17,458 confirmed HbSS cases, the pooled prevalence was 1.43% (95% CI: 1.08%–1.88%), with substantial heterogeneity (I 2 = 99.1%) and a prediction interval of 0.21%–8.91%. Central Africa showed the highest prevalence (1.99%), and Southern Africa showed the lowest (0.59%). Children exhibited a higher prevalence (1.65%) than adults (0.45%), while sex differences were non-significant (males 2.71%, females 1.74%; p = 0.694). The prevalence has remained stable over three decades despite a six-fold increase in research output, although wide prediction intervals indicated substantial between-study variability. Electrophoretic techniques predominated (86.4% of cases). Diagnostic method (χ² = 16.73, p = 0.033) and age category (χ² = 33.66, p < 0.0001) significantly moderated the prevalence. The multivariable meta-regression was marginally significant (χ² = 29.01, p = 0.066), but substantial residual heterogeneity persisted (I 2 = 98.6%). Leave-one-out sensitivity analysis showed that no single study significantly impacted the pooled estimates. Conclusion SCA represents a substantial and geographically variable public health challenge across Africa. These findings highlight the need for region-specific interventions, expanded newborn screening programs, improved diagnostic accessibility with quality assurance for point-of-care technologies, and continued surveillance to address geographic gaps.